2021
DOI: 10.1021/acssuschemeng.0c07292
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine-Modified Ru/TiO2 Catalyst for Selective Guaiacol Hydrodeoxygenation

Abstract: The selective hydrodeoxygenation of lignin-derived guaiacol to value-added products, especially phenol, under relatively mild reaction conditions remains an important challenge. A Cl-modified Ru/TiO 2 catalyst exhibited higher phenol selectivity compared with an unmodified one in the conversion of guaiacol in 1,4-dioxane at 240 °C and 1 MPa H 2 . Unlike Ru/TiO 2 , the modified catalyst exhibited a modest activity of demethoxylation producing phenol but an inferior ability of hydrogenation of its aromatic ring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 73 publications
3
24
1
Order By: Relevance
“…As reported in the literature, the binding energies of Ru 0 are located at 279.5-280.9 eV and those of Ru n+ are at 281.0-282 eV. 31,32 It is worth noting that as the Brønsted acid sites increased, the binding energy of Ru 0 gradually shifted to a higher value, indicating the Ru species on the surface became more electron-deficient (Fig. S4 †).…”
Section: Surface Acidic and Electronic Propertiessupporting
confidence: 63%
“…As reported in the literature, the binding energies of Ru 0 are located at 279.5-280.9 eV and those of Ru n+ are at 281.0-282 eV. 31,32 It is worth noting that as the Brønsted acid sites increased, the binding energy of Ru 0 gradually shifted to a higher value, indicating the Ru species on the surface became more electron-deficient (Fig. S4 †).…”
Section: Surface Acidic and Electronic Propertiessupporting
confidence: 63%
“…They interact strongly with unsaturated rings to induce hydrogenolysis and hydrogenation of unsaturated CC and CO bonds. [5][6][7] Our group has found that the redox sites of reducible metal oxides enable HDO reactions of the side groups of furans without ring-hydrogenation and ringopening. 8 The rate depends on the catalyst's ability to form oxygen vacancies while remaining stable under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Several exploratory catalyst studies for the selective conversion of guaiacol to demethoxylated phenolics have been reported in the literature. Examples are precious metal catalysts like PtÀ Sn/CNF/Inconel, [16] Pd/C, [17] TiO 2 supported Au, Ag, and Ru catalysts [18][19][20][21][22] but also cheaper Fe-based catalysts such as FeO x /CeO 2 , [23] supported Ni catalysts, [24,25] and Mo oxide catalysts [14,[26][27][28][29][30] , as shown in Table 1. Both batch set-up and fixed-bed reactors were used in previous studies.…”
Section: Introductionmentioning
confidence: 99%